Prevalence of Dyslipidemia and the Role of ApoB and hsCRP in Acute Myocardial Infarction: A Comprehensive Analysis: Dyslipidemia, ApoB, and hsCRP in Acute Myocardial Infarction - Farogh, Azfar; Iqbal, Zafar; Qaiser, Muhammad Affan; Hussain, Bushra; Fatima, Syeda Abeer; Akhter, Naheed (Pakistan Journal of Health Sciences, 2024)
Dyslipidemia significantly contributes to AMI, with ApoB and hsCRP offering potential for improved risk prediction. Objective: To determine the prevalence of dyslipidemia and the role of ApoB and hsCRP in acute myocardial infarction in patients presenting to a tertiary care hospital in Lodhran, Punjab. Methods: A cross-sectional study was conducted at the Department of Medicine, Shahida Islam Medical College, Lodhran, from May 2023 to November 2023. A total of 187 AMI patients aged 30–90 years were included using non-probability consecutive sampling. Data were collected using structured clinical history forms and laboratory analysis of lipid profiles, ApoB, and hsCRP levels. Dyslipidemia was defined using standard lipid cutoff values. Statistical analysis was performed using SPSS version 25.0, employing Chi-square and logistic regression to explore associations and predictors of dyslipidemia, with a significance level of p < 0.05. Results: Dyslipidemia was highly prevalent, affecting 74.9% of patients. Hypertension was significantly associated with dyslipidemia (OR = 2.049, p = 0.042), indicating a potential need for combined management strategies. ApoB and hsCRP levels did not show significant differences between dyslipidemic and non-dyslipidemic patients, though total cholesterol and LDL levels were significantly higher in the dyslipidemic group (p < 0.001). Conclusions: This study revealed a high prevalence of dyslipidemia in AMI patients, with hypertension as a key predictor. While ApoB and hsCRP were not significant discriminators, their roles in cardiovascular risk assessment may complement traditional lipid profiles, supporting personalized management strategies to reduce cardiovascular risk.